ANALISIS PENYUSUNAN LAPORAN KEUANGAN PESANTREN BERDASARKAN PEDOMAN AKUNTANSI PESANTREN - Suhaini, Suhaini; Arfan, Muhammad (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This research aims to determine and analyze the financial reports prepared by the Modern Maqamam Mahmuda Takengon Islamic boarding school and their conformity with the Islamic Boarding School Accounting Guidelines issued by Bank Indonesia and the Indonesian Accountants Association. This research is a type of case study research using a qualitative approach. The data sources used are primary and secondary data with data collection techniques using triangulation techniques consisting of interviews, observation, and documentation. The data analysis technique used is the Miles and Huberman model which consists of data reduction stages, data presentation, and concluding. The results indicate that the Maqamam Mahmuda Takengon Modern Islamic Boarding School has not prepared financial reports. The Maqamam Mahmuda Takengon Modern Islamic Boarding School only records cash receipts and disbursements. It is due to the lack of human resources owned by this Islamic boarding school and their ignorance of the Islamic Boarding School Accounting Guidelines as a reference in preparing their financial reports.